Two-dimensional nanocomposite electrochemiluminescence enhancer and preparation method thereof

By using two-dimensional nanocomposite materials of graphite phase carbon nitride doped with metal atoms and molybdenum disulfide as electrochemiluminescence enhancer, the luminescence intensity and stability of the luminous hydrogen peroxide system were solved, and efficient and stable electrochemiluminescence and high sensitivity detection effects were achieved.

CN119746909APending Publication Date: 2025-04-04CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411946215.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The lumino-hydrogen peroxide electrochemiluminescence system has problems such as low reactive oxygen generation efficiency, unstable intensity, easy decomposition of hydrogen peroxide and low utilization rate.

Method used

A two-dimensional nanocomposite material is used as an electrochemiluminescence enhancer. This material is prepared by a graphite phase carbon nitride as the substrate, doped with metal atoms (such as cobalt and iron) and combined with molybdenum disulfide.

Benefits of technology

The electrochemiluminescence intensity and stability of the luminol-hydrogen peroxide system are significantly improved, the sensitivity and accuracy of detecting hydrogen peroxide are improved, and dual potential chemiluminescence is achieved under neutral conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746909A_ABST
    Figure CN119746909A_ABST
Patent Text Reader

Abstract

The invention provides a two-dimensional nanocomposite electrochemical luminescence enhancer and a preparation method thereof. The composite material is of a nanosheet layer structure and comprises a monatomic catalyst and molybdenum disulfide, the mass ratio of the monatomic catalyst to the molybdenum disulfide is 1: 1, graphite phase carbon nitride serves as a substrate of the monatomic catalyst, metal atoms are doped in the graphite phase carbon nitride, and the metal atoms are one of cobalt (Co) and iron (Fe). The electrochemical luminescence enhancer can improve the electrochemical luminescence intensity of a luminol-hydrogen peroxide system, significantly improves the sensitivity and accuracy of hydrogen peroxide detection by an electrochemical luminescence analysis method based on the luminol-hydrogen peroxide system, and has great potential in the aspect of cancer cell detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemiluminescence, and in particular to a two-dimensional nanocomposite electrochemiluminescence enhancer and a preparation method and application thereof. Background Art

[0002] Electrochemiluminescence (ECL), also known as electrochemiluminescence, refers to the process in which a luminophore produces excited substances through a redox process, and these excited substances release energy in the form of light when they relax to a low-energy state. Electrochemiluminescence technology does not require the introduction of an external light source, avoids the interference of background light, has a high signal-to-noise ratio, and has good controllability and reproducibility. It is one of the best technologies for preparing biosensors. In the electrochemiluminescence system, luminol-hydrogen peroxide (luminol-H 2 O 2 ) system is widely used in biomedicine and clinical diagnosis due to its high luminescence intensity and fast response speed. However, it still has problems such as low efficiency of reactive oxygen generation, unstable intensity, easy decomposition of hydrogen peroxide and low utilization rate.

[0003] In view of this, researchers proposed to use electrochemiluminescence enhancers to enhance the intensity and stability of electrochemiluminescence. 3 N 4 ) is an effective electrochemiluminescence enhancer and is widely used in electrochemiluminescence sensors. 3 N 4 It is a non-metallic polymer two-dimensional semiconductor material. Although it has the advantages of good visible light response, adjustable structure, good stability, and rich surface functional groups, its electrode has obvious passivation phenomenon, which affects the stable electrochemiluminescence emission intensity. Therefore, a better electrochemiluminescence enhancer is urgently needed to enhance the intensity and stability of electrochemiluminescence. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a two-dimensional nanocomposite material as an electrochemiluminescence enhancer, as well as a preparation method and application of the electrochemiluminescence enhancer.

[0005] According to the first aspect, the present invention provides a two-dimensional nanocomposite material, which is a nanosheet structure and includes a single atom catalyst and molybdenum disulfide, wherein the mass ratio of the single atom catalyst to the molybdenum disulfide is 1:1, and the single atom catalyst is based on graphite phase carbon nitride, in which metal atoms are doped.

[0006] In some embodiments, the metal atom is one of cobalt (Co) and iron (Fe).

[0007] In some embodiments, the single atom catalyst is prepared by doping the metal atoms into the substrate by ultrasonication.

[0008] In some embodiments, the two-dimensional nanocomposite material is prepared by a one-step annealing method.

[0009] According to a second aspect, the present invention provides a method for preparing a two-dimensional nanocomposite material, comprising the following steps:

[0010] Step (1), annealing melamine in a muffle furnace to obtain graphite phase carbon nitride.

[0011] In some embodiments, the step specifically includes: placing melamine in a muffle furnace, heating it to 550°C at a heating rate of 5°C per minute, calcining it for two hours, and then cooling it naturally to obtain a calcined product. Grinding the calcined product to obtain graphite carbon nitride (gC 3 N 4 ) nanosheets.

[0012] Step (2), adding ethanol to the graphite phase carbon nitride to obtain a mixed solution; adding transition metal chloride to the mixed solution to obtain a reaction solution; subjecting the reaction solution to an ultrasonic reaction; and after the reaction is completed, stirring, filtering, washing with water, and drying are performed in sequence to obtain a single atom catalyst.

[0013] In some embodiments, this step specifically includes: 3 N 4 The nanosheets were dispersed in 40 ml of ethanol and pre-stirred for 6 hours to obtain a mixed solution. Transition metal chloride was added to the mixed solution and ultrasonically reacted for 1 hour to obtain a reaction solution; wherein gC 3 N 4 The feed ratio of the transition metal chloride is 1 g:0.01 mol. The reaction solution is stirred for 24 hours, filtered, washed with water, and dried at 110 degrees Celsius for 24 hours to obtain a single atom catalyst.

[0014] In some embodiments, the transition metal chloride is cobalt or iron chloride.

[0015] In some more specific embodiments, the cobalt or iron chloride is CoCl 2 6H 2 O, FeCl 3 ·5H 2 One of O.

[0016] Step (3), dispersing the single atom catalyst and molybdenum disulfide in ethanol, and obtaining a mixed solution after stirring and ultrasonic mixing; drying the mixed solution to obtain a precursor; placing the precursor in a tubular furnace for annealing, and grinding after annealing to obtain the two-dimensional nanocomposite material, wherein the mass ratio of the single atom catalyst to molybdenum disulfide is 1:1.

[0017] In some embodiments, the step specifically includes: mixing the single atom catalyst and molybdenum disulfide (MoS) at a mass ratio of 1:1. 2 ) is dispersed in 15 mL of ethanol, stirred for 1 hour and then ultrasonically mixed for 30 minutes to obtain a mixed solution; the mixed solution is dried at 100° C. for 2 hours to obtain a precursor; the precursor is heated to 400° C. in a tubular furnace at a heating rate of 5° C. per minute, calcined for two hours, and then naturally cooled, and the two-dimensional nanocomposite material is obtained after grinding.

[0018] According to a third aspect, the present invention provides a use of the two-dimensional nanocomposite material as described above, which is used as an electrochemiluminescence enhancer.

[0019] In some embodiments, the two-dimensional nanocomposite electrochemiluminescence enhancer is used in a luminol-hydrogen peroxide electrochemiluminescence system to increase the electrochemiluminescence intensity of the luminol-hydrogen peroxide system.

[0020] According to a fourth aspect, the present invention provides a method for using the two-dimensional nanocomposite electrochemiluminescence enhancer as described above in a luminol-hydrogen peroxide system, that is, an electrochemiluminescence method, comprising the following steps:

[0021] Step a, mixing the two-dimensional nanocomposite material, water, ethanol and a perfluorinated resin solution to obtain a suspension; wherein each 1 mL of the suspension contains 5 mg of the two-dimensional nanocomposite material; and applying the suspension on a polished glassy carbon electrode to obtain a modified electrode.

[0022] Step b, adding luminol suspension to a phosphate buffer solution to obtain a mixed solution; the pH value of the phosphate buffer solution is 7-8, and the concentration of the luminol suspension in the mixed solution is 0.0042 mmol / L.

[0023] Step c: adding H 2 O 2 solution, so that the mixture contains H 2 O 2 The concentration is 7.2 mol / L to obtain a luminol-hydrogen peroxide solution.

[0024] Step d, using a three-electrode system to power the luminol-hydrogen peroxide solution to achieve electrochemical luminescence; the three-electrode system includes: a working electrode is a modified electrode, a reference electrode is a silver / silver chloride electrode, and a counter electrode is a platinum electrode; the power supply adopts cyclic voltammetry, and the voltage is -1.6-0.6V.

[0025] The two-dimensional nanocomposite electrochemiluminescence enhancer provided by the present invention can improve the chemiluminescence intensity of the luminol-hydrogen peroxide system, and can significantly improve the sensitivity and accuracy of the electrochemiluminescence analysis method based on the luminol-hydrogen peroxide system to detect hydrogen peroxide, and has great potential in cancer cell detection sensing. In addition, the electrochemiluminescence enhancer can realize the bipotential chemiluminescence of the luminol-hydrogen peroxide system under neutral conditions, and exhibit a strong and stable luminescence effect. The preparation method of the two-dimensional nanocomposite provided by the present invention is simpler and safer than the traditional calcination method, and is easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 The single atom catalyst Co-C prepared in Example 1 of the present invention 3 N 4 , two-dimensional nanomaterials MoS 2 and composite materials MoS 2 / Co-C 3 N 4 Scanning electron microscope (SEM) photos of

[0028] Figure 2 The single atom catalyst Co-C prepared in Example 1 of the present invention 3 N 4 , two-dimensional nanomaterials MoS 2 and composite materials MoS 2 / Co-C 3 N 4 Transmission electron microscope (TEM) photograph;

[0029] Figure 3a Composite material MoS 2 / Co-C 3 N 4 One of the high-angle annular dark field scanning transmission (HAADF-STEM) images;

[0030] Figure 3bComposite material MoS 2 / Co-C 3 N 4 The second HAADF-STEM image shows the single-atom Co bright spots marked with circles;

[0031] Figure 3c Composite material MoS 2 / Co-C 3 N 4 The third HAADF-STEM image shows the distribution of Co elements;

[0032] Figure 4 gC prepared in Example 1 and Example 2 3 N 4 、Co-C 3 N 4 、Fe-C 3 N 4 X-ray diffraction (XRD) spectrum;

[0033] Figure 5 gC prepared in Example 1 3 N 4 、MoS 2 、Co-C 3 N 4 、MoS 2 / Co-C 3 N 4 XRD spectrum of

[0034] Figure 6a gC prepared in Example 1 3 N 4 、MoS 2 、MoS 2 / Co-C 3 N 4 X-ray photoelectron spectroscopy (XPS) overall spectrum;

[0035] Figure 6b gC 3 N 4 With MoS 2 / Co-C 3 N 4 C1s spectrum of

[0036] Figure 6c gC 3 N 4 With MoS 2 / Co-C 3 N 4 N1s spectrum;

[0037] Figure 6dMoS 2 With MoS 2 / Co-C 3 N 4 Mo 3d spectrum;

[0038] Figure 6e MoS 2 With MoS 2 / Co-C 3 N 4 S2p spectrum of

[0039] Figure 6f MoS 2 / Co-C 3 N 4 Co 2p spectrum;

[0040] Figure 7 For the use of bare electrodes, Co-C 3 N 4 、Fe-C 3 N 4 、MoS 2 / Co-C 3 N 4 、MoS 2 / Fe-C 3 N 4 Luminol-H 2 O 2 Comparison chart of electrochemiluminescence intensity of the system electrochemiluminescence instrument;

[0041] Figure 8 Because bare electrodes are used, MoS 2 / Co-C 3 N 4 and MoS 2 / Fe-C 3 N 4 Luminol-H 2 O 2 Voltage / luminescence intensity spectrum of the system's electrochemiluminescence instrument;

[0042] Fig. 9 MoS at different luminol concentrations 2 / Co-C 3 N 4 -luminol-H 2 O 2 Electrochemiluminescence intensity diagram of the system;

[0043] Fig.10 For different H 2 O 2 MoS at concentrations 2 / Co-C3 N 4 -luminol-H 2 O 2 Electrochemiluminescence intensity diagram of the system;

[0044] Fig.11 MoS at different pH values 2 / Co-C 3 N 4 -luminol-H 2 O 2 Electrochemiluminescence intensity diagram of the system;

[0045] Fig.12 Composite material MoS 2 / Co-C 3 N 4 Electrochemical luminescence intensity diagram after 10 cyclic voltammetry tests;

[0046] Fig.13 MoS 2 / Co-C 3 N 4 -luminol-H 2 O 2 System and MoS 2 / Co-C 3 N 4 Cyclic voltammetric characteristic curve of -luminol-DO system;

[0047] Fig.14 MoS 2 / Co-C 3 N 4 -luminol-H 2 O 2 Electron paramagnetic resonance spectrum of the system;

[0048] Fig.15 MoS 2 / Co-C 3 N 4 -luminol-H 2 O 2 System and MoS 2 / Fe-C 3 N 4 -luminol-H 2 O 2 In situ FT-IR spectrum of the system under electrochemical conditions;

[0049] Fig.16 MoS 2 / Co-C 3 N 4-luminol-H 2 O 2 Schematic diagram of the electrochemiluminescence mechanism of the system;

[0050] Fig.17 For the electrochemiluminescence enhancer Co-C 3 N 4 The relationship curve between the concentration of cancer cell lysate and the electrochemiluminescence intensity under the action of. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.

[0052] The applicant has found that single-atom catalysts (SACs) have unique advantages in catalytic activity and selectivity in various catalytic reactions. Compared with traditional catalysts, SACs have the highest metal utilization efficiency and the lowest metal raw material consumption. At the same time, by utilizing different active sites and adjustable coordination environments, SACs exhibit excellent catalytic activity and unique selectivity for the corresponding reactions, and these advantages fully match the application requirements of electrochemiluminescence enhancers.

[0053] The applicant also found that in order to improve gC 3 N 4 The activity can be improved by doping with metal or non-metal elements and in gC 3 N 4 The method of constructing a heterojunction structure with other semiconductors. Among them, MoS2 is a 3 N 4 One of the most ideal choices for building heterojunction structures, MoS 2 The large interlayer spacing of MoS is conducive to the rapid transfer of electrons and ions, and the two-dimensional layered structure and two-dimensional heterojunction can provide higher charge mobility. 2 With gC 3 N 4 The well-matched energy band positions ensure better electrochemical performance.

[0054] Based on the above findings, in order to avoid gC 3 N 4 In the case of passivation defects under electrochemical conditions, the present invention adopts the following solution ideas: firstly, gC 3 N 4 As the base, using gC 3 N 4 The abundant active sites are doped with metal single atoms to form SACs with high catalytic activity and high selectivity. 2Combined with the composite material, the electron transfer efficiency was improved to obtain a two-dimensional nanocomposite electrochemiluminescence enhancer. Finally, the electrochemiluminescence enhancer was applied to luminol-hydrogen peroxide (luminol-H 2 O 2 ) system to verify its luminescence enhancement effect. The results show that with transition metal cobalt or iron as the central atom, gC 3 N 4 SACs and MoS as supports 2 The composite material can effectively promote the luminol-H 2 O 2 The system produces reactive oxygen species, which in turn enhances the luminol-H 2 O 2 Electrochemiluminescence performance of the system.

[0055] The above is the concept of the two-dimensional nanocomposite electrochemical luminescence enhancer provided by the present invention. Based on the above concept, the present invention selects transition metal Co or Fe as the central atom, C 3 N 4 As a carrier, single-atom catalysts were prepared by ultrasonic method, and then the single-atom catalysts were mixed with MoS 2 After mixing, the mixture was placed in a tube furnace for one-step annealing to prepare a two-dimensional nanocomposite electrochemiluminescence enhancer, and its effect on luminol-H 2 O 2 Electrochemical luminescence enhancement effect of the system. The following is a detailed introduction of the two-dimensional nanocomposite electrochemical luminescence enhancer provided by the present invention and its preparation method and application in combination with the embodiments.

[0056] The following is a detailed introduction to the preparation method of the two-dimensional nanocomposite electrochemiluminescence enhancer provided by the present invention in conjunction with the embodiments. The preparation method comprises the following steps:

[0057] Step (1), annealing melamine in a muffle furnace to obtain graphite phase carbon nitride;

[0058] Step (2), adding ethanol to the graphite phase carbon nitride to obtain a mixed solution; adding transition metal chloride to the mixed solution to obtain a reaction solution; subjecting the reaction solution to an ultrasonic reaction; and after the reaction is completed, stirring, filtering, washing with water, and drying are performed in sequence to obtain a single atom catalyst.

[0059] Step (3), dispersing the single atom catalyst and molybdenum disulfide in ethanol, and obtaining a mixed solution after stirring and ultrasonic mixing; drying the mixed solution to obtain a precursor; placing the precursor in a tubular furnace for annealing, and grinding after annealing to obtain the two-dimensional nanocomposite material.

[0060] A specific implementation of the above steps is described below, namely, the two-dimensional nanocomposite MoS 2 / Co-C 3 N 4 The preparation process.

[0061] Example 1 Two-dimensional nanocomposite material MoS 2 / Co-C 3 N 4 Preparation

[0062] Step (1), 4g melamine (C 3 H 6 N 6 ) was placed in a ceramic crucible and placed in a muffle furnace, heated to 550°C at a heating rate of 5°C per minute, and then calcined for two hours and then cooled naturally to obtain a calcined product. The calcined product was ground into powder to obtain gC 3 N 4 Nanosheets.

[0063] Step (2), 1g of gC prepared in step (1) 3 N 4 The nanosheets were dispersed in 40 mL of ethanol and pre-stirred for 6 hours to obtain a mixed solution; 0.01 mol of CoCl 2 6H 2 O, and a reaction solution was obtained after ultrasonic reaction for 1 hour, the ultrasonic power was 300 W, and the ultrasonic treatment frequency was 80 kHz; the reaction solution was stirred for 24 hours, vacuum filtered, and washed three times with 500 mL of distilled water, and then the filter paper containing the filtered product was placed in a culture dish and sealed with plastic wrap, and dried in an oven at 110° C. for 24 hours to obtain a single atom catalyst Co-C 3 N 4 .

[0064] Step (3), dispersing 1g of the prepared single atom catalyst and 1g of molybdenum disulfide in 15mL of ethanol, stirring for 1 hour and then ultrasonically mixing for 30 minutes to obtain a mixed solution, wherein the ultrasonic power is 300W and the ultrasonic treatment frequency is 80kHz; drying the mixed solution in an oven at 100°C for 2 hours to obtain a precursor; placing the precursor in a ceramic crucible, introducing nitrogen into a tubular furnace, heating the precursor to 400°C at a heating rate of 5°C per minute, calcining the mixture for two hours, and then cooling the mixture naturally, and grinding the mixture to obtain the two-dimensional nanocomposite material MoS 2 / Co-C 3 N 4 .

[0065] Example 2 Two-dimensional nanocomposite material MoS 2 / Fe-C 3 N 4Preparation

[0066] The preparation process is the same as that of Example 1, except that CoCl 2 6H 2 O replaced by FeCl 3 ·5H 2 O.

[0067] The above is the preparation method of the two-dimensional nanocomposite electrochemiluminescence enhancer provided by the present invention. The structural characteristics of the two-dimensional nanocomposite material provided by the present invention are introduced below in conjunction with specific embodiments.

[0068] Figure 1 This is a scanning electron microscope (SEM) photograph of the product prepared in Example 1 above. Figure 1 a is the single atom catalyst Co-C 3 N 4 SEM photos of Figure 1 b is two-dimensional nanomaterial MoS 2 SEM photos of Figure 1 c is a two-dimensional nanocomposite material MoS 2 / Co-C 3 N 4 SEM photograph of.

[0069] Figure 2 This is a transmission electron microscope (TEM) photograph of the product prepared in Example 1 above. Figure 2 a is the single atom catalyst Co-C 3 N 4 TEM photos of Figure 2 b is two-dimensional nanomaterial MoS 2 TEM photos of Figure 2 c is a two-dimensional nanocomposite material MoS 2 / Co-C 3 N 4 TEM photo of.

[0070] According to the SEM and TEM images, it can be seen that the two-dimensional nanocomposite MoS prepared according to the above Example 1 2 / Co-C 3 N 4 It has a nanosheet structure.

[0071] Figure 3a Figure 3b and Figure 3c The two-dimensional nanocomposite material MoS prepared in Example 1 above 2 / Co-C 3 N 4 The high-angle annular dark field scanning transmission (HAADF-STEM) image clearly shows that MoS 2 / Co-C 3 N 4 Characteristics of Co metal single atom dispersion in composite materials.

[0072] Figure 4 The gC prepared in Examples 1 and 2 above 3 N 4 、Co-C 3 N 4 、Fe-C 3 N 4 By comparison, it can be seen that the Co-C prepared in Example 1 and Example 2 3 N 4 、Fe-C 3 N 4 Compared with gC without single atom doping 3 N 4 Compared with the absence of other characteristic peaks, it proves that the metal atoms have not agglomerated and are dispersed in the gC in the form of single atoms. 3 N 4 On the base.

[0073] Figure 5 gC prepared in Example 1 3 N 4 、MoS 2 、Co-C 3 N 4 、MoS 2 / Co-C 3 N 4 XRD spectrum of MoS 2 / Co-C 3 N 4 gC can be found in the XRD pattern 3 N 4 The characteristic peaks of 100 and 002 crystal planes and MoS 2 The characteristic peaks of 002, 100, 103, and 110 are Figure 4 No new characteristic peaks appeared in the MoS 2 / Co-C 3 N 4 The composite synthesis was successful.

[0074] Figure 6a gC prepared in Example 1 3 N 4 、MoS 2 、MoS 2 / Co-C 3 N 4The XPS overall spectrum shows that the presence of C, N, Mo, S and Co elements can be clearly observed. Figure 6b gC 3 N 4 With MoS 2 / Co-C 3 N 4 The C1s spectrum of Figure 6c gC 3 N 4 With MoS 2 / Co-C 3 N 4 The N1s spectrum of Figure 6b and Figure 6c By comparison, it can be found that in the composite material MoS 2 / Co-C 3 N 4 In the experiment, the bonding form of C and N did not change significantly. However, the C=NC bond showed a chemical shift of 1.64 eV, proving that the single atom Co and N formed a chemical bond.

[0075] Figure 6d MoS 2 With MoS 2 / Co-C 3 N 4 Mo 3d spectrum, Figure 6e MoS 2 With MoS 2 / Co-C 3 N 4 The S2p spectrum of Figure 6d and 6e In the Mo 3d and S2p spectra shown, MoS 2 It has the same characteristic peaks as the composite material, but the composite material MoS 2 / Co-C 3 N 4 The characteristic peaks of MoS 2 There is a chemical shift of about 0.33-0.34 eV compared with the characteristic peak of 2 Combination occurred, further confirming that MoS 2 With Co-C 3 N 4 successful compound.

[0076] Figure 6f MoS 2 / Co-C 3 N 4The Co 2p spectrum of MoS shows four peaks. The peaks at 785.8 eV and 800 eV correspond to Co 2p3 / 2 and Co 2p1 / 2, respectively, and the peak at 785.8 eV can be attributed to the Co-N bond. The double peaks at 791.3 eV and 804.3 eV indicate that MoS 2 Co was successfully doped and a Co-S bond was formed. Based on the above analysis, it can be inferred that the N-Co-S structure forms a chemical connection.

[0077] The structural characteristics of the two-dimensional nanocomposite material provided by the embodiment of the present invention are introduced above. Next, three experiments will be conducted to demonstrate the application effect of the two-dimensional nanocomposite electrochemiluminescence enhancer prepared by the embodiment of the present invention in the luminol-hydrogen peroxide electrochemiluminescence system, and to introduce how to adjust the solution to obtain a better luminescence effect.

[0078] Experiment 1: By comparing the changes in the electrochemiluminescence spectrum of the luminol-hydrogen peroxide system under different electrochemiluminescence enhancers, the electrochemiluminescence enhancer prepared in the embodiment of the present invention on the electrochemiluminescence enhancement in the reaction of hydrogen peroxide and luminol was verified. Specifically, the bare electrode, gC 3 N 4 、Co-C 3 N 4 、Fe-C 3 N 4 、MoS 2 / Co-C 3 N 4 、MoS 2 / Fe-C 3 N 4 In luminol-H 2 O 2 The electrochemiluminescence intensity in the system was used to verify the MoS 2 / Co-C 3 N 4 and MoS 2 / Fe-C 3 N 4 Luminol-H 2 O 2 Enhancement of electrochemiluminescence at positive potential of the system.

[0079] The experimental conditions are as follows: the electrochemiluminescence enhancer to be tested, water, ethanol and perfluorinated resin (Nafion) solution are mixed to obtain a suspension; wherein each 1 mL of the suspension contains 5 mg of the electrochemiluminescence enhancer, and the ratio of water, ethanol and Nafion is water: ethanol: Nafion = 20:79:1; 5 μL of the suspension is evenly coated on a glassy carbon electrode polished with alumina polishing powder to obtain a modified electrode.

[0080] Wherein, the electrochemical luminescence enhancer to be tested is Co-C prepared in Example 1 or Example 2 3 N 4 、Fe-C 3 N 4 、MoS 2 / Co-C 3 N 4 、MoS 2 / Fe-C 3 N 4 In addition, a bare electrode without the addition of an electrochemiluminescence enhancer was also tested as a control.

[0081] Prepare 500 mL of phosphate buffer solution (PBS solution), add 300 μL of luminol suspension with a concentration of 7 mmol / L, so that the concentration of luminol in the mixed solution is 0.0042 mmol / L, and obtain a mixed solution; wherein the pH value of the phosphate buffer solution is 7.4. Take 10 mL of the mixed solution, add 1 mL of H 2 O 2 solution, so that the mixture contains H 2 O 2 The concentration is 7.2 mmol / L to obtain a luminol-hydrogen peroxide solution as the electrolyte.

[0082] The electrochemical luminescence properties of luminol-hydrogen peroxide were tested using a three-electrode system, and the working mode of the electrochemical workstation was a cyclic voltammetry test. The three-electrode system includes: a modified electrode as the working electrode, a silver / silver chloride (Ag / AgCl) electrode as the reference electrode, and a platinum (Pt) electrode as the counter electrode. The cyclic voltammetry voltage was set to -1.6-0.6V. The luminescence effect was detected using an electrochemical luminescence instrument photomultiplier tube, and its voltage was set to 850V.

[0083] The experimental results are as follows Figure 7 As shown, it can be seen that in MoS 2 / Co-C 3 N 4 Under the enhancement of luminol-H 2 O 2 The electrochemical luminescence intensity of the system is the largest, about 13022 (counts). Bare electrode, Co-C 3 N 4 、Fe-C 3 N 4 and MoS 2 / Fe-C 3 N 4 Under the action of luminol-H 2 O 2The electrochemiluminescence intensities of the systems were 3571 (counts), 2287 (counts), 486 (counts) and 7813 (counts), respectively.

[0084] Experiment 2: Detect the change of luminescence intensity of luminol-hydrogen peroxide system with voltage, and prove the enhancement effect of electrochemical luminescence enhancer provided by the embodiment of the present invention on the luminescence of the system at different potentials.

[0085] Specifically, the bare electrode, MoS 2 / Co-C 3 N 4 and MoS 2 / Fe-C 3 N 4 Catalytic luminol-H 2 O 2 The relationship between the voltage and luminescence intensity of the system was used to investigate the effect of electrochemiluminescence enhancer on luminol-H 2 O 2 The effect of electrochemiluminescence of the system on positive and negative potentials.

[0086] The experimental conditions are different from those of Experiment 1 in that the electrochemical luminescence enhancer to be tested is MoS prepared in Example 1 or Example 2. 2 / Co-C 3 N 4 or MoS 2 / Fe-C 3 N 4 In addition, a bare electrode without electrochemiluminescence enhancer was tested as a control. The test content is the relationship between luminescence intensity and voltage. Other experimental conditions are the same as those in Experiment 1.

[0087] Using bare electrodes, MoS 2 / Co-C 3 N 4 and MoS 2 / Fe-C 3 N 4 The voltage / luminescence intensity spectrum of the electrochemiluminescence instrument is as follows Figure 8 As shown. The electrochemiluminescence enhancer MoS was used 2 / Co-C 3 N 4 The electrochemiluminescence instrument showed the strongest electrochemiluminescence intensity at the positive potential of 0.48V and the negative potential of -1.17V, with the anode luminescence intensity of about 19507 (counts) and the cathode luminescence intensity of about 7046 (counts). Figure 8 The oxidation peak and reduction peak of the dual potential electrochemical luminescence can be determined. The anodic ECL luminescence is observed at the luminol oxidation peak at 0.48 V, while the H2 O 2 Cathodic ECL luminescence was observed at the reduction peak.

[0088] The electrochemiluminescence enhancer MoS was used 2 / Fe-C 3 N 4 The electrochemiluminescence instrument also produced bipotential luminescence at the same position, but the intensity was relatively weak, with the anode luminescence intensity of about 6940 (counts) and the cathode luminescence intensity of about 348 (counts). The bare electrode only showed a luminescence intensity of about 3663 (counts) at the anode. This shows that the electrochemiluminescence enhancer MoS provided by the present invention is 2 / Fe-C 3 N 4 and MoS 2 / Co-C 3 N 4 Can help luminol-H 2 O 2 The system realizes dual-potential electrochemiluminescence, and the electrochemiluminescence of the system can be enhanced at both positive and negative potentials.

[0089] Experiment 3: The optimal reaction concentration of the luminescence system was obtained by adjusting the concentrations of hydrogen peroxide and luminol as well as the pH value of the solution.

[0090] Under the electrochemiluminescence enhancer concentration, photomultiplier tube voltage and scanning potential determined in Experiments 1 and 2 above, the electrochemiluminescence intensity of the system is similar to that of luminol and H 2 O 2 The concentration of luminol and H showed a certain correlation with the pH value of the mixed solution. In order to obtain the best linear relationship and achieve the best electrochemiluminescence enhancement effect, this experiment investigated luminol and H 2 O 2 Effects of concentration and pH value on electrochemiluminescence.

[0091] The experimental conditions are different from those of Experiment 1 in that the electrochemical luminescence enhancer to be tested is MoS prepared in Example 1. 2 / Co-C 3 N 4 The electrolyte was prepared as follows: 500 mL of phosphate buffer solution (PBS solution) was prepared, and 300 μL of luminol suspension with a concentration of a mmol / L was added to obtain a mixed solution; wherein the pH value of the phosphate buffer solution was c. 10 mL of the mixed solution was taken, and 1 mL of b mmol / L -1 H 2 O 2 Solution.

[0092] The concentrations or pH values ​​at a, b, and c are replaced according to the following experimental content:

[0093] (1) Fixed 60mmol·L -1 H 2 O 2 and pH 7. The luminol concentration a ranged from 1 to 9 mmol·L -1 .

[0094] (2) Fixed 5mmol·L -1 luminol and pH 7. 2 O 2 The investigation range of concentration b is 20-100mmol·L -1 .

[0095] (3) Fixed 5mmol·L -1 luminol and 60mmol·L -1 H 2 O 2 The investigation range of pH value c is 3-11.

[0096] Other experimental conditions were the same as those in Experiment 1.

[0097] The experimental results are as follows Fig. 9 , Fig.10 and Fig.11 shown.

[0098] like Fig. 9 As shown in the figure, when other conditions remain unchanged, at a luminol concentration of 7 mmol·L -1 When the concentration of luminol is increased, the electrochemical luminescence intensity is the strongest. Continuing to increase the concentration of luminol will cause the luminescence intensity to gradually decrease.

[0099] like Fig.10 As shown, when other conditions remain unchanged, 2 O 2 Concentration: 80mmol·L -1 When H 2 O 2 concentration, the luminous intensity will gradually decrease.

[0100] like Fig.11 As shown, when other conditions remain unchanged, the electrochemiluminescence intensity is strongest at a pH value of 11.

[0101] According to the above results, when luminol and H 2 O 2When the concentration is too low, sufficient reactive oxygen species cannot be produced, resulting in a weak luminescence signal. 2 O 2 When the concentration is too high, the higher concentration will quench the luminescence. As for the pH value, the greater the alkalinity, the higher the luminescence intensity, but in order to meet the needs of the subsequent preparation of the biosensor, pH 7 was selected as the pH value for subsequent testing.

[0102] The above experiments show that the optimal reaction condition is to add 7mmol·L -1 luminol, 80mmol·L -1 H 2 O 2 , electrolyte pH = 7, where MoS 2 / Co-C 3 N 4 The concentration of 4 mg / mL and the electrode coating volume of 5 μL can obtain MoS with better luminescence effect. 2 / Co-C 3 N 4 -luminol-H 2 O 2 system.

[0103] Under the above conditions, MoS 2 / Co-C 3 N 4 -luminol-H 2 O 2 The system was tested 10 times in succession to verify the MoS 2 / Co-C 3 N 4 -luminol-H 2 O 2 The electrochemiluminescence intensity stability of the system. Fig.12 As shown, after 10 cycles, MoS 2 / Co-C 3 N 4 -luminol-H 2 O 2 The anodic luminescence of the system can still remain stable, with a relative standard deviation (RSD) of 2.27%.

[0104] The above demonstrates the application effect of the electrochemiluminescence enhancer provided by the present invention in the luminol-hydrogen peroxide electrochemiluminescence system, and the experiment verifies that the electrochemiluminescence enhancer can enhance the luminescence intensity of the luminol-hydrogen peroxide system. Next, the reaction mechanism of the electrochemiluminescence enhancer enhancing the luminescence of the luminol-hydrogen peroxide system will be introduced.

[0105] (1) Whether dissolved oxygen (DO) is involved in the reaction was investigated. 2 / Co-C 3 N 4 -luminol-H 2 O 2 System and MoS 2 / Co-C 3 N 4 -luminol-DO system was tested for cyclic voltammetry (CV), and the results were as follows Fig.13 As shown, MoS 2 / Co-C 3 N 4 The -luminol-DO system shows a reduction peak at -0.431 V, which can be attributed to the oxygen reduction reaction. 2 / Co-C 3 N 4 -luminol-H 2 O 2 The reduction peak at -1.17 V observed in the system corresponds to the H 2 O 2 This indicates that MoS 2 / Co-C 3 N 4 Mainly activates H 2 O 2 This produces a higher concentration of reactive oxygen species (ROS), thereby enhancing the ECL intensity.

[0106] (2) Electron paramagnetic resonance (EPR) experiments were conducted to explore the two active oxygen free radicals OH and O 2 · - In MoS 2 / Co-C 3 N 4 -luminol-H 2 O 2 The system realizes dual potential luminescence. 5,5-Dimethyl-1-pyrrolidine N-oxide (DMPO) is used as ·OH and O 2 · - DMPO reacts with these free radicals to form DMPO-·OH and DMPO-O 2 · -Spin adducts, which showed characteristic quaternary EPR signals of 1:2:2:1 and 1:1:1:1, respectively. Without adding luminol as a co-reactant, the characteristic peaks corresponding to the active oxygen generated under positive and negative potentials were detected in situ. The results are as follows Fig.14 As shown, the ·OH and O 2 · - The corresponding EPR signals indicate that both radicals contribute to the ECL emission at the anode and cathode. 2 · - The intensity of ·OH is greater than that of ·OH, while at negative potentials, the intensities of the two signal peaks are comparable, indicating that the cathode luminescence involves ·OH and O 2 · - , while O 2 · - Dominate in anode luminescence.

[0107] (3) In situ FT-IR was used to study the 2 O 2 In the electrochemiluminescence enhancer MoS 2 / Co-C 3 N 4 and MoS 2 / Fe-C 3 N 4 Adsorption behavior on the interface.

[0108] Electrochemiluminescence enhancer MoS 2 / Co-C 3 N 4 The In situ FT-IR results are as follows Fig.15 a, 3100 to 3400 cm -1 The characteristic band between is MoS 2 / Co-C 3 N 4 The absorption peak increases with the increase of negative potential, indicating that MoS 2 / Co-C 3 N 4 It has a strong affinity for water and hydrogen peroxide in solution, thus promoting the cleavage of the OO bond and the formation of the ·OH intermediate. 850cm -1 The peak at 2 · - / *O 2 - ) corresponds to the adsorbed hydrogen peroxide molecules (*H 2 O 2). It is worth noting that this absorption peak only begins to appear at -1.0 V, which is consistent with the H observed in the CV data at the same potential. 2 O 2 The reduction peak corresponds to 1110cm -1 The absorption peak at is attributed to the stretching vibration of the adsorbed peroxy (OOH / *OOH) intermediates, which can be efficiently converted into ROS.

[0109] MoS 2 / Fe-C 3 N 4 The In situ FT-IR test results are as follows Fig.15 As shown in b, compared with MoS 2 / Co-C 3 N 4 In comparison, MoS 2 / Fe-C 3 N 4 At 3100 to 3400 cm -1 The -OH peaks between them are much weaker, which indicates that they are 2 O 2 The adsorption capacity of 1040cm -1 The absorption peak at is attributed to *OOH, but its intensity is relatively weak. From a macroscopic point of view, MoS 2 / Fe-C 3 N 4 For H 2 O 2 The adsorption capacity is lower than that of MoS 2 / Co-C 3 N 4 .

[0110] According to the above experimental results and analysis, MoS 2 / Co-C 3 N 4 -luminol-H 2 O 2 The electrochemiluminescence mechanism of the system is as follows Fig.16 As shown, MoS 2 / Co-C 3 N 4 The electrochemiluminescence enhancer promotes the cleavage of the OO bond and accelerates the generation of the OOH intermediate, converting the hydrogen peroxide molecule into O 2 - and ·OH radicals, the two radicals react with luminol at the cathode and anode respectively, thus causing bipotential electrochemical luminescence. 2 / Co-C 3 N 4 -luminol-H2 O 2 The specific process of electrochemiluminescence of the system is as follows:

[0111] Cathodoluminescence:

[0112] H 2 O 2 +e - → OH+O 2 · - (1)

[0113] LH - + OH → L - +H 2 O (2)

[0114] L. - +O 2 · - →LO 2 2- (3)

[0115] LO 2 2- →AP 2 2- *+N 2 (4)

[0116] AP 2 2- * →AP 2 2- +hν (5)

[0117] Anode luminescence:

[0118] LH - -e - →L - +H + (6)

[0119] L. - +O 2 · - →LO 2 2- (7)

[0120] LO 2 2- →AP 2 2- *+N 2 (8)

[0121] AP 2 2- * →AP 2 2- +hν (9)

[0122] The asterisk indicates the excited state.

[0123] The above describes the reaction mechanism of the electrochemiluminescence enhancer provided by the embodiment of the present invention to enhance the luminescence of the luminol-hydrogen peroxide system. Next, the application of the electrochemiluminescence enhancer in actual detection is introduced.

[0124] Due to the overexpression of hydrogen peroxide in cancer cells, the presence of cancer cells can be detected based on the concentration of hydrogen peroxide in cell lysate. Based on this principle, the H2O2 concentration in the lysate of human liver cancer cells (HepG2 cells) was measured. 2 O 2 The test results are as follows: Fig.17 As shown in Figure 2, with the increase of hydrogen peroxide concentration, the electrochemiluminescence signal gradually increased and showed good linearity, with a linear range of 5 μmol·L -1 -100μmol·L -1 , y=18.87x+32.91, R 2 =0.9927, and the detection limit is 0.018 μmol·L -1 , which is approximately equivalent to 4 cells.

[0125] The above introduces the practical application of the electrochemiluminescence enhancer provided by the present invention in cancer cell detection.

[0126] From the above content, it can be seen that the electrochemiluminescence enhancer provided by the present invention has the following beneficial effects:

[0127] 1. The electrochemiluminescence enhancer provided by the present invention can significantly improve the chemiluminescence intensity of the luminol-hydrogen peroxide system, and can be used to improve the sensitivity and accuracy of the electrochemiluminescence analysis method based on the luminol-hydrogen peroxide system to detect hydrogen peroxide.

[0128] 2. The electrochemiluminescence enhancer provided by the present invention can realize the bipotential chemiluminescence of the luminol-hydrogen peroxide system under neutral conditions and exhibit a strong and stable luminescence effect.

[0129] 3. The material preparation method provided by the present invention is simpler, safer and easier to industrialize than the traditional calcination method.

[0130] In the description of the embodiments of the present application, words such as "exemplary", "for example" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary", "for example" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary", "for example" or "for example" is intended to present related concepts in a concrete way.

[0131] In the description of the embodiments of the present application, the term "and / or" is merely a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, B exists alone, and A and B exist at the same time. In addition, unless otherwise specified, the term "plurality" means two or more.

[0132] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the specification and claims of this application, unless otherwise expressly stated, the singular forms "a", "an" and "the" include plural forms. The terms "include", "comprise", "have" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.

[0133] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present application, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present application have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present application, any method, equipment, and material of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present application can also be used to realize the present application.

[0134] The specific implementation methods described above further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above embodiments are only illustrative of the principles and effects of the present application, and are not intended to limit the present application. Anyone familiar with this technology can modify or change the above embodiments without violating the spirit and scope of the present application. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed in the present application should still be covered by the claims of the present application.

Claims

1. A two-dimensional nanocomposite material, characterized in that: The composite material is a nanosheet structure, comprising a single-atom catalyst and molybdenum disulfide, wherein the mass ratio of the single-atom catalyst to the molybdenum disulfide is 1:1, and the single-atom catalyst is based on graphite phase carbon nitride, in which metal atoms are doped.

2. A two-dimensional nanocomposite material according to claim 1, characterized in that: The metal atom is one of cobalt (Co) and iron (Fe).

3. The two-dimensional nanocomposite material according to claim 1, characterized in that The single atom catalyst is prepared by doping the metal atoms into the substrate through an ultrasonic method.

4. The two-dimensional nanocomposite material according to claim 1, characterized in that The two-dimensional nanocomposite material is prepared by a one-step annealing method.

5. A method for preparing a two-dimensional nanocomposite material, characterized in that: The steps include: Melamine is annealed in a muffle furnace to obtain graphite phase carbon nitride; Adding ethanol to the graphite phase carbon nitride to obtain a mixed solution; adding transition metal chloride to the mixed solution to obtain a reaction solution; subjecting the reaction solution to an ultrasonic reaction; and after the reaction is completed, stirring, filtering, washing with water, and drying are performed in sequence to obtain a single atom catalyst; The single atom catalyst and molybdenum disulfide are dispersed in ethanol, and a mixed solution is obtained after stirring and ultrasonic mixing; the mixed solution is dried to obtain a precursor; the precursor is placed in a tube furnace for annealing, and after annealing, the precursor is ground to obtain the two-dimensional nanocomposite material; Wherein, the mass ratio of the single atom catalyst to molybdenum disulfide is 1:

1.

6. The preparation method according to claim 5, characterized in that: The transition metal chloride is cobalt or iron chloride.

7. The preparation method according to claim 6, characterized in that: The cobalt or iron chloride is one of CoCl2·6H2O and FeCl3·5H2O.

8. The use of the two-dimensional nanocomposite material according to claim 1, characterized in that: Used as an electrochemiluminescence enhancer.

9. The use according to claim 8, characterized in that The two-dimensional nanocomposite electrochemiluminescence enhancer is used in a luminol-hydrogen peroxide electrochemiluminescence system.

10. An electrochemiluminescence method, characterized in that: The method is carried out using the two-dimensional nanocomposite material as described in any one of claims 1 to 4 and applied to a luminol-hydrogen peroxide system, comprising the following steps: The two-dimensional nanocomposite material, water, ethanol and a perfluorinated resin solution are mixed to obtain a suspension; wherein each 1 mL of the suspension contains 5 mg of the two-dimensional nanocomposite material; 5 μL of the suspension is applied to a polished glassy carbon electrode to obtain a modified electrode; Adding luminol suspension to a phosphate buffer solution to obtain a mixed solution; the pH value of the phosphate buffer solution is 7-8, and the concentration of luminol suspension in the mixed solution is 0.0042 mmol / L; adding H2O2 solution to the mixed solution to make the concentration of H2O2 in the mixed solution 7.2 mmol / L, to obtain a luminol-hydrogen peroxide solution; Electrochemical luminescence can be achieved by supplying power to the luminol-hydrogen peroxide solution using a three-electrode system; the three-electrode system includes: a modified electrode as a working electrode, a silver / silver chloride electrode as a reference electrode, and a platinum electrode as a counter electrode; the power supply adopts cyclic voltammetry, and the voltage is -1.6-0.6V.

Citation Information

Cited By

  • ECL-based MoS2 nano material vacancy defect identification method

    CN120490067A